Importance of the monomer–dimer–tetramer interconversion of the clock protein KaiB in the generation of circadian oscillations in cyanobacteria. (10th December 2014) - Iida, Takahiro; Mutoh, Risa; Onai, Kiyoshi; Morishita, Megumi; Furukawa, Yukio; Namba, Keiichi; Ishiura, Masahiro
<x xml:space="preserve">Abstract</x> The molecular machinery of the cyanobacterial circadian clock oscillator consists of three proteins, KaiA, KaiB and KaiC, which interact with each other to generate circadian oscillations in the presence of ATP (the in vitro KaiABC clock oscillator). KaiB comprises four subunits organized as a dimer of dimers. Our previous study suggested that, on interaction with KaiC, the tetrameric KaiB molecule dissociates into two molecules of dimeric KaiB. It is uncertain whether KaiB also exists as a monomer and whether the KaiB monomer can drive normal circadian oscillation. To address these questions, we constructed a new KaiB oligomer mutant with an N‐terminal deletion, KaiB10–108. KaiB10–108 was a monomer at 4 °C but a dimer at 35 °C. KaiB10–108 was able to drive normal clock oscillation in an in vitro reconstituted KaiABC clock oscillator at 25 °C, but it was not able to drive normal circadian gene expression rhythms in cyanobacterial cells at 41 °C. Wild‐type KaiB existed in equilibrium between a dimer and tetramer at lower KaiB concentrations or in the presence of 1 m NaCl. Our findings suggest that KaiB is in equilibrium between a monomer, dimer and tetramer in cyanobacterial cells.